Extreme Precipitation Depiction in Convection‐Permitting Earth System Models Within the nextGEMS Project - Jonathan D. Wille; Rebekka Koch; Tobias Becker; Erich Fischer (Journal of Advances in Modeling Earth Systems, 2025)
Abstract As extreme precipitation events become more frequent and intense, local‐scale climate services are increasingly needed to help communities adapt. We here evaluate two fully coupled convection‐permitting Earth System Models for their ability to resolve mesoscale extreme weather events. Using the Integrated Forecasting System (IFS) and Icosahedral Nonhydrostatic Weather and Climate Model (ICON) within the Next Generation Earth Modeling Systems (nextGEMS) project, we evaluate their depiction of extreme precipitation with a focus on the Mediterranean region through a comparison with high resolution reanalysis, gridded observations, a regional climate model, and two lower‐resolution climate models. The results are then compared at a common, coarser resolution globally. For dry extremes, we find that the higher resolution and hybrid/explicit representation of convection of the nextGEMS models improve the representation of dry day fraction over land by about 5%–7% points. Generally, the nextGEMS models concentrate dry spells into limited frequency yet overly long periods, although the lack of convection parameterization in ICON reduces maximum annual dry spell length over land by 45 days compared to a lower‐resolution model version. For wet extremes, the nextGEMS models properly high intensities of heavy precipitation, aside from overestimation in ICON over mountainous terrain. ICON, with no convection scheme, tends to create overly intense, small, convective cells that are triggered without moisture convergence. Overall, the depiction of wet and dry precipitation extremes in the Mediterranean region are representative of the nextGEMS' models performance across the global mid‐latitudes demonstrating the models' value in simulating extreme weather systems.